Resibufogenin Suppresses Triple-Negative Breast Cancer Angiogenesis by Blocking VEGFR2-Mediated Signaling Pathway - Yang, Ting; Jiang, Yi-Xin; Wu, Ye; Lu, Dong; Huang, Rui; Wang, Long-Ling; Wang, Shi-Qi; Guan, Ying-Yun; Zhang, Hong; Luan, Xin (Frontiers in Pharmacology, 2021)
Resibufogenin (RBF), an active compound from Bufo bufonis, has been used for the treatment of multiple malignant cancers, including pancreatic cancer, colorectal cancer and breast cancer. However, whether RBF could exert its anti-tumor effect by inhibiting angiogenesis remains unknown. Here, we aimed to explore the anti-angiogenic activity of RBF and its underlying mechanism on human umbilical vein endothelial cell (HUVEC), and the therapeutic efficacy with regard to anti-angiogenesis in vivo using two triple-negative breast cancer (TNBC) models. Our results demonstrated that RBF can inhibit the proliferation, migration and tube formation of HUVECs in a dose-dependent manner. Spheroid sprouts were thinner and shorter after RBF treatment in vitro 3D spheroid sprouting assay. RBF also significantly suppressed VEGF-mediated vascular network formation in vivo Matrigel plug assay. In addition, western blot analysis was used to reveal that RBF inhibited the phosphorylation of VEGFR2 and its downstream protein kinases FAK and Src in endothelial cells (ECs). Molecular docking simulations showed that RBF affected the phosphorylation of VEGFR2 by competitively binding to the ATP-bound VEGFR2 kinase domain, thus preventing ATP from providing phosphate groups. Finally, we found that RBF exhibited promising anti-tumor effect through anti-angiogenesis in vivo without obvious toxicity. The present study firstly revealed the high anti-angiogenic activity and the underlying molecular basis of RBF, suggesting that RBF could be a potential antiangiogenic agent for angiogenesis-related diseases.